The Impact of Tax Benefits on the Improvement of Special Economic Zones - Abdukakhorov Bekzod Utkir Ugli (Central Asian Journal of Theoretical and Applied Science, 2022)
The article considers the role of tax benefits in the further improvement of the Special Economic Zones operating in the Republic of Uzbekistan, organization of the investment climate and its improvement, as well as the issues of activation of attraction of foreign direct investment to the economic sectors of the country.